Toward the 24 hour large SAG Mill Reline - John Russell (Canadian Institute of Mining, Metallurgy and Petroleum, 2008)
"Faster, safer, grinding mill relining offers the obvious attractions of reduced mill relining times with the knock-on incentive to reduce all other maintenance down-time, opening the possibility for increased annual plant utilisation.Leading edge liner handler technologies by RME, focused toward even shorter relines for very large SAG and AG mills, have recently split into two quite distinct paths:•,?Single SAG/AG Mill Relining Machines (MRM’s) of very large capacity, such as Newcrest Cadia’s 40’ SAG MRM of 6000 kg capacity and P.T. Freeport’s 38’/34’ SAG MRM of 7250 kg capacity;•,?Twin-machine SAG/AG Mill Relining Systems of moderate to large capacity such as BHP Billiton’s Escondida Laguna Seca 38’ SAG MRM’s, each featuring 4500 kg capacity.RME, its customers noted above and their liner suppliers are providing leadership in this important annual utilisation advance.Once the 24 hour mill shell reline becomes reality, liners designed for maximum profit, not maximum life, albeit exchanged more frequently, become possible too.INTRODUCTIONAt most mineral grinding plants, mill relining activities dictate each maintenance shutdown’s critical path. When annualized, mill relining remains the largest, single influence in defining plant availability.Because of restricted access, both inside and outside the mill, increased application of manual labour has no effect on reducing relining downtime. The only answer for RME has been to develop and apply new relining technologies now known as RME’s Mill Relining System.RME’s primary focus for over twenty years has been the reduction of grinding mill relining times while simultaneously providing a marked improvement in relining safety. Our original (1990) target was to halve traditional (pre-RME) reline times and to eliminate accidents and injury by mechanizing all physical work."